Reduced Expression of Prion Protein With Increased Interferon-β Fail to Limit Creutzfeldt-Jakob Disease Agent Replication in Differentiating Neuronal Cells - Aguilar, Gerard; Pagano, Nathan; Manuelidis, Laura (Frontiers in Physiology, 2022)
Immortalized uninfected septal (SEP) neurons proliferate but after physiological mitotic arrest they express differentiated neuronal characteristics, including enhanced cell-to-cell membrane contacts and >8 fold increases in host prion protein (PrP). We compared proliferating uninfected and Creutzfeldt-Jakob Disease (CJD) agent infected cells with their arrested counterparts over 33 days by quantitative mRNA and protein blot analyses. Surprisingly, uninfected arrested cells increased interferon-(IFN- mRNA by 2.5-8 fold; IFN- mRNA elevations were not previously associated with neuronal differentiation. SEP cells with high CJD infectivity titers produced a much larger 40-68 fold increase in IFN- mRNA, a classic host anti-viral response that is virucidal for RNA but not DNA viruses. High titers of CJD agent also induced dramatic decreases in host PrP, a protein needed for productive agent replication. Uninfected arrested cells produced large sustained 20-30 fold increases in PrP mRNA and protein whereas CJD arrested cells showed only transient small 5 fold increases in PrP. A >10 fold increase in infectivity, but not PrP misfolding, induced host PrP reductions that can limit CJD agent replication. In contrast to neuronal lineage cells, functionally distinct migratory microglia with high titers of CJD agent do not induce an IFN- mRNA response. Because they have 1/50th the PrP of an average brain cell, microglia would be unable to produce the many new infectious particles needed to induce a large IFN- response by host cells. Instead, microglia and related cells can be persistent reservoirs of infection and spread. Phase separations of agent-associated molecules in neurons, microglia and other cell types can yield new insights into the molecular structure, persistent and evasive behavior of CJD-type agents.